Hazard analysis of unemployment duration by gender in a developing country: The case of Turkey - Aysit Tansel; H. Mehmet Taşçi (Institute for the Study of Labor (IZA), 2010)
There is little evidence on unemployment duration and its determinants in developing countries. This study is on the duration aspect of unemployment in a developing country, Turkey. We analyze the determinants of the probability of leaving unemployment for employment or the hazard rate. The effects of the personal and household characteristics and the local labor market conditions are examined. The analyses are carried out for men and women separately. The results indicate that the nature of unemployment in Turkey exhibits similarities to the unemployment in both the developed and the developing countries.
Keywords: J64; C41; J16; 330; Unemployment duration; hazard analysis; gender; Turkey; Arbeitslosigkeit; Dauer; Geschlecht; Statistische Bestandsanalyse; Türkei